Halal Tourism In Bali: Pengaruh Dan Tantangan Mengembangkan Wisata Halal Di Bali - Amalia Fiqia Wandhini,Astri Dwi Dayanti, Lailatul Nafiah,Iskandar (ACTIVA: Jurnal Ekonomi Syariah, 2019)
This research is shown to explain how the role of tourists or halal tourism in Bali. Bali is a tourist spot that is very popular with many tourists from domestic and abroad. So from that the government has one program to increase Muslim tourists. One of them is the area of ​​Bali, but the area of ​​Bali is famous for its very strong culture and the majority of its religion is also Hindu where the Muslim population there is only 30% less. That is what makes halal tourism in Bali difficult to implement. This study uses qualitative methods, and uses a variety of processes in data collection including: Questionnaires and Literature Review, which deals with discussions to answer the problem. The results of this study indicate that Halal Tourism can develop if the government Suggestions from this study, can be realized in Bali Nuanced Mosques, Sharia Beaches, Sharia Hotels, and Halal Restaurants Therefore, this journal tries to analyze the existence of Halal Tourism when applied in Bali.